Implementasi Pendidikan Inklusi Pada Sekolah Dasar Islam Terpadu Al-Firdaus Banjarmasin - Barsihanor, Barsihanor; Anindia Rosyida, Desy (Jurnal Tarbiyatuna, 2019)
This study aims to determine the implementation and inhibiting factors of the implementation of inclusive education in the Al-Firdaus Integrated Islamic Elementary School Banjarmasin. The research method used is a qualitative approach, and the type of research is case studies. The research informants were the school principal, inclusive school coordinator, class teacher, teacher assistant (special teacher), and students. The results of the study found the implementation of inclusive education in the Al-Firdaus Banjarmasin Integrated Islamic Elementary School including, 1). planning, each teacher is required to make lesson plans individually learning. 2). implementation, learning patterns carried out in the inclusive class consisted of three activities; tahfidz learning, regular classes, individual learning programs. 3). assessment, the school distinguishes the content of the questions and the difficulty level of the questions. Obstacles in the implementation of inclusive education at SDIT Al-Firdaus Banjarmasin occur in the implementation of learning in between classroom management and teachers need to repeatedly explain the material to students who are slow learners.